137k views
1 vote
Rewrite the function by completing the square F(x)=2x^2+3x-2

User Ftl
by
4.8k points

2 Answers

4 votes

y = 2 ( x + 3/4 )^2 − 25 8

User Pthalacker
by
4.9k points
1 vote

Answer:


\boxed{ \ 2(x+(3)/(4))^2-(25)/(8)\ }

Explanation:

we should write this function


2x^2+3x-2

this way
a(x-b)^2+c

let s check the first terms in
x^2 and x


2x^2+3x

this is the beginning of


2(x+(3)/(4))^2

indeed


2(x+(3)/(4))^2=2x^2+3x+2((3)/(4))^2=2x^2+3x+(9)/(8)

so we can write that


2x^2+3x=2(x+(3)/(4))^2-(9)/(8)

then


2x^2+3x-2=2(x+(3)/(4))^2-(9)/(8)-2=2(x+(3)/(4))^2-(9+16)/(8)=2(x+(3)/(4))^2-(25)/(8)

User Artur Carvalho
by
4.6k points